2002
DOI: 10.1074/jbc.m205872200
|View full text |Cite
|
Sign up to set email alerts
|

Potassium-evoked Glutamate Release Liberates Arachidonic Acid from Cortical Neurons

Abstract: Ischemic cell death in the brain accompanies any condition characterized by a significant interruption in cerebral blood flow, including stroke and head trauma. Although many of the cellular and molecular mechanisms that lead to ischemic cell death have been described, efficacious methods of intervention remain elusive. Brain levels of free fatty acids, specifically arachidonic acid (AA), 1 can be released rapidly during cerebral ischemia and can reach up to 10-fold higher concentrations than levels estimated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 55 publications
1
37
0
Order By: Relevance
“…4 and 5). The failure of tetanus toxin, a Clostridium toxin that prevents evoked, but not spontaneous, synaptic vesicle exocytosis in our and other systems (23)(24)(25)(26), to reduce both constitutive neuronal activity and basal COX-2 mRNA expression in our cultures (Fig. 6) led us to conclude that spontaneous synaptic activity regulates basal neuronal COX-2 expression.…”
Section: Discussionmentioning
confidence: 95%
“…4 and 5). The failure of tetanus toxin, a Clostridium toxin that prevents evoked, but not spontaneous, synaptic vesicle exocytosis in our and other systems (23)(24)(25)(26), to reduce both constitutive neuronal activity and basal COX-2 mRNA expression in our cultures (Fig. 6) led us to conclude that spontaneous synaptic activity regulates basal neuronal COX-2 expression.…”
Section: Discussionmentioning
confidence: 95%
“…Depolarizing concentrations of K ϩ promote active release of AA in cortical neurons (15), retina (16), and synaptosomes (17). One interpretation of these results is that high K ϩ promotes a depolarization-dependent Ca 2 ϩ influx through voltage-gated Ca 2 ϩ channels.…”
Section: Cyclooxygenase-2-generated Prostaglandin E2 Modulates Postsymentioning
confidence: 86%
“…One interpretation of these results is that high K ϩ promotes a depolarization-dependent Ca 2 ϩ influx through voltage-gated Ca 2 ϩ channels. This in turn activates presynaptic glutamate release that modulates excitatory glutamate receptors (15). Thus Ca 2 ϩ influx through the N -methyl-d -aspartate (NMDA) receptor, and direct Ca 2 ϩ entrance through voltage-dependent calcium channels, activate phospholipase A 2 (PLA 2 ) to result in AA release via phospholipid hydrolysis.…”
Section: Cyclooxygenase-2-generated Prostaglandin E2 Modulates Postsymentioning
confidence: 99%
“…Phospholipase A2 inhibitors prevent the increase in superoxide following DCD Ionomycin, metabolic inhibition or glutamate have each been reported to activate phospholipase A2 in CGNs (Lazarewicz et al 1990;Gunasekar et al 1995;Chen et al 1999) and cortical neurons (Tapia-Arancibia et al 1992;Stella et al 1995;Taylor and Hewett 2002) while PLA2 inhibitors decrease cell death measured by lactic dehydrogenase release (Ciani et al 1996). In addition Lafon-Cazal et al (1993) reported that superoxide production from glutamate-exposed CGNs was due in part to arachidonic acid release.…”
Section: (A) (B)mentioning
confidence: 99%